Towards a collection of cost-effective technologies in support of the NIST cybersecurity framework - Shackleton, Bruce Michael Stuart (Rhodes University, Faculty of Science, Department of Computer Science, 2018)
The NIST Cybersecurity Framework (CSF) is a specific risk and cybersecurity framework. It provides guidance on controls that can be implemented to help improve an organisation's cybersecurity risk posture. The CSF Functions consist of Identify, Protect, Detect, Respond, and Recover. Like most Information Technology (IT) frameworks, there are elements of people, processes, and technology. The same elements are required to successfully implement the NIST CSF. This research specifically focuses on the technology element. While there are many commercial technologies available for a small to medium sized business, the costs can be prohibitively expensive. Therefore, this research investigates cost-effective technologies and assesses their alignment to the NIST CSF. The assessment was made against the NIST CSF subcategories. Each subcategory was analysed to identify where a technology would likely be required. The framework provides a list of Informative References. These Informative References were used to create high- level technology categories, as well as identify the technical controls against which the technologies were measured. The technologies tested were either open source or proprietary. All open source technologies tested were free to use, or have a free community edition. Proprietary technologies would be free to use, or considered generally available to most organisations, such as components contained within Microsoft platforms. The results from the experimentation demonstrated that there are multiple cost-effective technologies that can support the NIST CSF. Once all technologies were tested, the NIST CSF was extended. Two new columns were added, namely high-level technology category, and tested technology. The columns were populated with output from the research. This extended framework begins an initial collection of cost-effective technologies in support of the NIST CSF.
Keywords: National Institute of Standards and Technology (U.S.); Computer security; Computer networks -- Security measures; Small business Information technology -- Cost effectiveness; Open source software